Researching Resistance : Public Education after Neoliberalism. - Huckaby, M. Francyne (Qualitative Inquiry: Critical Ethics, Justice and Activismseries Is a Collection Designed to Provide a Cross-Disciplinary Overview of the Use of Qualitative Research As an Avenue for Justice and Critical Transformative Activism/action Socially, Enviro., 2019)
"This book serves two vital functions. First, it explores, explicates, and encourages critical qualitative research that engages the arts and born-digital scholarship. Second, it offers options for understanding neoliberalism, revealing its impact on communities, and resisting it as ideology, practice, and law. The book delves into: strategies for engaging neoliberalism; the Black feminist cyborg theoretical assumptions and intentions of the ethnographic web-based film project; the research and arts-based methodology that walks the fault line between film and ethnography, and; the relationships between the researcher, the activist organizations, and the activism. While the book will focus on neoliberalism within the realm of public education, the implications extend to many other areas of public life."--